A Preliminary Study on the Motivation of Funders for Crowdfunding - Teresia Debby; Mustika Sufiati Purwanegara; Atik Aprianingsih (School of Business, IPB University (SB-IPB), 2019)
Crowdfunding is a new and novel way to gather fund through the internet for small and medium-size business from many investors. It is different from the conventional method which capital is gained from the loans from some of the conventional financial institutions like banks, angel investors, venture capitalists. Even though it is very popular, there are few numbers of researches have been done on this topic, especially to identify the motivation behind someone when investing in using this method. Some studies have been done to explore motivations. In this study, the sampling techniques that will be used are convenience and snowball sampling techniques. In the end, the study can gather 68 respondents, which all responses would be analyzed using an exploratory analysis using R software. Based on the results, there are five groups of motivations for investing in crowdfunding; they are enjoyment, recognition, curiosity, perceived risk, and altruism. The results of this study provided theoretical implications for future research and practical implications for the success of crowdfunding platforms.Keywords: crowdfunding, crowd-funding, funding motivation, crowdfunding motivation, internet based funding